EQ + SQ = ST2: a spiritually intelligent approach to actor training part one – the 12 principles. Issue 1 (2nd January 2018) - Hensey, Jane
Abstract: This article explores the links between current psychological concepts of emotional and spiritual intelligence and Stanislavskian-influenced actor training. Using the 12 principles of spiritual intelligence (SQ) as a prism through which to conflate the ideas of a variety of practitioners, the author seeks to address some of the more challenging drivers in contemporary drama training – reduced hours, merging methodologies, learner diversity, and the rise of mental health issues in young people. As science continues to elucidate and articulate the intuitions of Stanislavski and his associates, an understanding and practical application of the qualities associated with SQ will help our next generation of actors experience an education that offers both context and technique alongside focused development of the individual, both as the self and as the artist. Current trainers have a responsibility to prepare students not just to "act well" but also to "work well" and – most importantly – to "live well" and this paper seeks to contribute to pedagogical discourse around the question of "how?"